Aid Policy and the Macroeconomic Management of Aid. (May 2015) - Addison, Tony; Tarp, Finn
Summary: This is an introduction to the UNU-WIDER special issue of World Development on aid policy and the macroeconomic management of aid. We provide an overview of the 10 studies, grouping them under three sub-themes: the aid–growth relationship; the supply-side of aid (including its level, volatility, and coordination of donors); and the macroeconomic framework around aid. The studies in the special issue demonstrate the centrality of research methodology, the importance of disaggregation, and the need to account for country-specific situations and problems. This introduction concludes that the sometimes "over heated" debate on aid needs redirecting toward more rigorous analysis, in which the advantages—and disadvantages—of using aid for development can be evaluated in a calmer manner.